Experimental investigations of the response of suction caissons to transient combined loading - Byrne, B; Houlsby, G (2004)
Combined loading of foundations is a fundamental problem in civil engineering, particularly in the offshore industry where harsh environmental conditions occur. Large moment and horizontal loads may be applied to the foundation as well as vertical loads. Also, as the waves pass a structure, there can be rapid changes in the loads, so that transient effects need to be considered. When designing shallow foundations, such as suction caissons, there is uncertainty in the current understanding of how the foundation responds to these loads. This paper presents experiments, performed on model suction caisson foundations, where typical cyclic loading conditions are applied. The footing is embedded in oil-saturated sand so that dimensionless drainage times are comparable with the typical offshore conditions. Most of the testing was carried out with the vertical load held constant, to mimic the structural dead weight, while realistic "pseudorandom" moment and horizontal cyclic loads were applied. Experiments were carried out at different vertical loads, showing that the response depends on the vertical load level. Nondimensional relationships were established which accounted for this dependency. Surprisingly, the rate of loading had little impact on the load-displacement behavior for the experiments undertaken. © ASCE/MARCH 2004.